Effects of Self-Concept on Narcissism: Mediational Role of Perceived Parenting - Farzand, Maryam; Cerkez, Yagmur; Baysen, Engin (Frontiers in Psychology, 2021)
Increase in narcissism has been reported by experts over the years. Narcissists bring lot of negative consequences to themselves and to people around them. The present study aimed at exploring effects of perceived parenting and self-concept in the development of narcissistic traits and how adults view and carry parenting effects throughout their lives. A sample of 628 adults were taken from North Cyprus through purposive sampling. Scales for perceived parenting, self-concept and narcissism were administered. Results showed narcissism is predicted by both perceived parenting and self-concept. Several constituents of perceived parenting and self-concept interconnect in order to exhibit the distinctive narcissistic traits of an individual. It clarifies and speaks for the need of further research in establishing the basis by which perceived parenting may lead to underdeveloped self-concept which in turn result in narcissistic traits. The study findings also have challenged the notion of only mothers to be responsible for narcissistic traits among their children.